Amyloidosis of the small intestine - Kala, Zdenek; Válek, Vlastimil; Kysela, Petr (European journal of radiology, 2007)
UNLABELLED: Amyloidosis is a rare disease characterized by forming pathological protein deposits - amyloid - in many organs and tissues. This decreases their functionality. The aim of this small study was to determine, whether the radiological picture of the small intestine involvement in amyloidosis is in some sense specific as sometimes described in literature giving rise to high suspicion for the disease in symptomatic patients. MATERIAL AND METHODS: The prospective study comprising seven patients hospitalized in surgical department is presented together with a survey on the disease, its appearance in radiological imaging. All patients underwent abdominal ultrasound (ATL 5000 HDI, 7-12MHz linear probe, no contrast enhancement, supine position), abdominal CT (Somatom Plus, Siemens, single detector, conventional abdominal CT protocol) and enteroclysis (Micropaque suspension 300ml, application rate of 75ml/min, dilution with HP-7000 being 1:1 and HP-7000 solution 2000ml, application rate of 120ml/min.). RESULTS: The amyloid deposits in the small intestine could be visualized in five of seven patients with the disease. Enteroclysis revealed a diffuse slowed down intestinal motility with an obstruction-like picture in all of our seven patients. The intestinal secretion was normal, plicae were getting polyp-like shape in five of them forming so called "thumb printing" picture. CT showed thickening of the intestinal wall due to deposits with poor blood supply and contrast retention in five of seven patients. Ultrasound visualized thickened, hypoechoic nodular plicae and slowed down motility in these five patients. The most striking finding was the pathological deposits in the intestinal wall were highly hypo-vascular. However, this picture is very similar to that of ischemic enteritis. All seven patients had proven amyloid deposits from bioptic specimens. CONCLUSION: The diagnosis of amyloidosis must be supported by bioptic examination as it has no pathognomic radiological picture. Nevertheless, it allows usually to rise a high suspicion for this and sometimes even guess the type of the pathological protein involved. This can start a search for the primary reason of possible amyloidosis and thus perhaps spear the patients quality of life.
Keywords: počítačová rentgenová tomografie; kontrastní látky; Amyloidosis; Sensitivity and Specificity; senzitivita a specificita; síran barnatý; Humans; Rare Diseases; Image Enhancement; Contrast Media; Intubation, Gastrointestinal; tenké střevo; Intestinal Diseases; Prospective Studies; Ultrasonography; lidé; dyspepsie; nemoci střev; gastrointestinální intubace; amyloidóza; Intestine, Small; ultrasonografie; Barium Sulfate; Tomography, X-Ray Computed; prospektivní studie; vzácné nemoci; Dyspepsia; vylepšení obrazu